Job satisfaction during COVID-19: industry 5.0 as a driver of sustainable development and gender equality - Frutos-Bencze, Dinorah; Sokolova, Marcela; Zubr, Vaclav; Mohelska, Hana (Technological and Economic Development of Economy, 2022)
Employee job satisfaction is essential for organizations because it influences motivation as well as productivity, and consequently the overall performance of an organization. As the COVID-19 pandemic disrupted many work-related processes and practices, the Industry 5.0 framework formulated new approaches for a sustainable and resilient European industry. The aim of this study is to evaluate the effects of the pandemic on job satisfaction in terms of gender differences and firm size in the context of the Industry 5.0 paradigm. Job Satisfaction Surveys (JSS) from the year 2013 to 2021 were analyzed. Our results indicate that in the Czech Republic, overall job satisfaction did not decline during the pandemic, and women were slightly more satisfied than men. Moreover, overall job satisfaction was slightly higher in small firms. These are surprising results, given the negative impacts on employment reported by many countries. We explore the differences in government policies and programs enacted during the pandemic to assist employers and employees to mitigate the negative impacts of the pandemic. In general, Czech and EU policies appeared to be better in mitigating unemployment rates than US policies. The findings are valuable for crafting best practices for organizations and future policy and program planning for governments.